Auxiliary motion training system based on wireless human pose computer vision estimation algorithm - Gong, Yaoze; Gong, Jiankun; You, Ting (Edelweiss Applied Science and Technology, 2025)
With the advancement of science and technology, many technologies are gradually being used in various aspects. In terms of sports, computer vision has been comprehensively utilized, making training more effective. Human pose estimation reflects various information regarding the dynamics of the body by establishing the similarity between different parts of the human body, such as angles and positions. The purpose of this paper is to study a computer vision estimation algorithm based on wireless human pose and to combine it with image processing. By scanning human body information through the computer, basic information about the person and the corresponding images can be obtained, allowing for the estimation of human joint posture. In terms of methodology, compared with traditional training methods, the results showed that training under computer vision improved the accuracy of joint data by 16%, the accuracy of coaches’ judgments on athletes by 15%, and the performance of students by 14.8%. In conclusion, it was also shown that the auxiliary training system based on wireless computer vision was beneficial to the training of athletes and could help trainees train more scientifically and effectively.